GRADUONYMIC RELATIONS IN PHRASEOLOGICAL UNITS WITH THE WORD "ANGER" (INTERNATIONAL CONFERENCE ON MODERN DEVELOPMENT OF PEDAGOGY AND LINGUISTICS, 2026)
This article discusses the idea that phraseological units expressing the seme “anger” occupy an important place in the emotional-expressive layer of the language, that these units express the mental state of a person to different degrees and create graduonymic relations based on mutual semantic proximity. There is information about semantic relations between units related to the states of intensification and decrement in the process of gradation. The fact that graduonymic relations in phraseologisms with the seme “anger” reveal the internal semantic hierarchy of the phraseological system is proven by examples.